Pengembangan E-LKPD Berbasis Learning Cycle 7E dan Pengaruhnya Terhadap Pemahaman Konsep dan Keterampilan Proses Sains Peserta Didik - Chaerunnisa Luvitasari Firdausi; Kristian Handoyo Sugiyarto; Yusup Maulana (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to develop e-SW or e-LKPD products, test the feasibility of e-SW 7E products based on expert assessments, test the practicality of e-SW 7E products based on the assessment of chemistry teachers and peer reviewers, find out the responses of students in terms of readability and test the effectiveness of e-SW 7E products. The method in this research is R&D with a 4-D development model. The sampling technique used in this study used cluster random sampling techniques. Interviews, questionnaires, and question techniques carry out data collection techniques. The data analysis technique used is the assessment of theoretical validity by qualitative experts converted quantitatively using the Likert scale with a score range of 1-5, empirical validity analyzed using the Quest program, and manova test analysis using SPSS. The results of the study found that e-SW 7E based on learning cycle 7E feasible, practical student responses in terms of readability in the very good category resulted in an average of all aspects of 4.45 and a percentage of 82.5%. There was an effects on the understanding of concepts and skills of the science process by 34.5%.